Physics, consciousness and transcendence: The physics of Roger Penrose and David Bohm as regards a scientific explanation of the human mind open to reality - Béjar Gallego, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The works of David Bohm and Roger Penrose per se represent a major contribution to the study of physics and consciousness. It is not an easy task to engage in rigorous analysis of one of the most profound philosophical-scientific problems; namely explaining the nature of consciousness. This article explores the global vision that emerges from Bohm and Penrose’s approach to physics and consciousness. It focuses on examining the way in which their respective physical-metaphysical proposals can be bound together in a general model, thus shedding more light on the phenomenological characteristics of consciousness. The philosophical consequences of this model are closer in many respects to the experience of transcendence as described in religious works. What emerges is a unitary image of man in the cosmos that harmonises notions of mind and matter, open to a transcendent connection between the conscious subject and reality.